2022
DOI: 10.3389/fcell.2022.901093
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Glial Reaction and Altered Neuronal Nitric Oxide Synthase are Implicated in Attention Deficit Hyperactivity Disorder

Abstract: Attention deficit hyperactivity disorder (ADHD) has a complex etiology, and its specific causal factors remain to be elucidated. Aberration of nitric oxide synthase (nNOS) and inflammation, together with astrocytic and microglial cells have been continually associated with several neurological disorders, including ADHD. Using spontaneously hypertensive rat (SHR), we investigated the changes in nNOS, inflammatory, microglial and astrocytic markers in the frontal cortex and hippocampus at three different ages: o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…Microglia activation was previously described in the spontaneously hypertensive rat ( Zhang et al, 2022 ), and the 6-OHDA mouse ( Meseguer-Beltrán et al, 2023 ) models of ADHD. We decided to verify microglia reactivity in our conditions, and to investigate the consequences of P2X4 deletion on microglia changes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microglia activation was previously described in the spontaneously hypertensive rat ( Zhang et al, 2022 ), and the 6-OHDA mouse ( Meseguer-Beltrán et al, 2023 ) models of ADHD. We decided to verify microglia reactivity in our conditions, and to investigate the consequences of P2X4 deletion on microglia changes.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a genome-wide associated study identified causal genes for ADHD in microglia ( Fahira et al, 2019 ). Accordingly, microglia reactivity in ADHD conditions has been already demonstrated in humans ( Yokokura et al, 2021 ) and animal models ( Song et al, 2021 ; Zhang et al, 2022 ; Sanches et al, 2023 ). Recent evidence for microglia reactivity has been also provided in the ACC of the 6-OHDA mouse model ( Meseguer-Beltrán et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immuno-fluorescence staining was used to detect the activation of CA1 in the hippocampus and microglia in the prefrontal cortex. Compared with normal rats, the expression of CA1 in the hippocampus and microglia in the prefrontal cortex of the SHRs was significantly increased [ 182 ]. This suggests that microglia may be involved in the pathogenesis of ADHD.…”
Section: The Role and Influence Of Gut Metabolites In Neuroinflammati...mentioning
confidence: 99%
“…The mechanisms leading to the catecholaminergic disruption observed in this disorder are multifactorial [ 16 ] and yet to be clarified. Increased glial activity has been reported in murine models of ADHD [ 17 , 18 ], suggesting involvement of glial cells in the functional and structural changes preceding ADHD symptoms. The glial function is essential for neuronal pruning and firing [ 6 , 19 ], network connectivity during development, and the secretion of pro-inflammatory and anti-inflammatory cytokines [ 20 ].…”
Section: Introductionmentioning
confidence: 99%